2010
DOI: 10.1073/pnas.1006098107
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of invasiveSalmonellavia bacterial-induced extrusion of mucosal epithelia

Abstract: Salmonella enterica is an intracellular bacterial pathogen that resides and proliferates within a membrane-bound vacuole in epithelial cells of the gut and gallbladder. Although essential to disease, how Salmonella escapes from its intracellular niche and spreads to secondary cells within the same host, or to a new host, is not known. Here, we demonstrate that a subpopulation of Salmonella hyperreplicating in the cytosol of epithelial cells serves as a reservoir for dissemination. These bacteria are transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
536
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(602 citation statements)
references
References 43 publications
(32 reference statements)
47
536
3
1
Order By: Relevance
“…18,19 Remarkably, in some instances both lifestyles are observed in the same infected cell. 18 The exact signals that drive S. Typhimurium to colonize the cytosol of the infected epithelial or to remain enclosed in a phagosomal compartment, remain unknown. Factors that may potentially predispose to a precise intracellular lifestyle in the pathogen include the phase of cell cycle in the host cell at the time it is invaded and/or an intrinsic variability in gene expression in the invading bacterium.…”
Section: Pathogen and Host Variability During Infectionmentioning
confidence: 92%
See 2 more Smart Citations
“…18,19 Remarkably, in some instances both lifestyles are observed in the same infected cell. 18 The exact signals that drive S. Typhimurium to colonize the cytosol of the infected epithelial or to remain enclosed in a phagosomal compartment, remain unknown. Factors that may potentially predispose to a precise intracellular lifestyle in the pathogen include the phase of cell cycle in the host cell at the time it is invaded and/or an intrinsic variability in gene expression in the invading bacterium.…”
Section: Pathogen and Host Variability During Infectionmentioning
confidence: 92%
“…As the infection progresses in epithelial cells, subpopulations of cytosolic and intra-vacuolar intracellular bacteria evolve having distinct expression profiles for virulence determinants encoded by Salmonellapathogenicity islands 1 and 2 (SPI1 and SPI2). 18 These two intracellular lifestyles have been reported both in cultured epithelial cells and in vivo in enterocytes of infected mice. 18,19 Remarkably, in some instances both lifestyles are observed in the same infected cell.…”
Section: Pathogen and Host Variability During Infectionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been known for several years that a small percentage of Salmonella escape from the vacuole and reside in the cytosol of epithelial cells [38]. Recent work has shown that the bulk of Salmonella replication observed during growth in epithelial cells occurs in the cytosol; the significance of this during infection is unknown although it may play a role in bacterial dissemination [39,40]. Escape from the vacuole has also been observed for Mycobacterial species and L. pneumophila suggesting that an extra-vacuolar stage occurs in other bacterial infections [41][42][43].…”
Section: Vacuole Disruption As a Survival Strategymentioning
confidence: 99%
“…In the mouse model of infection, bacteria reside in various cells of the immune system 10 or epithelial cells of the intestinal tract and gallbladder. 11 Low numbers of Salmonella have also been found in nonphagocytic stromal cells of the intestinal lamina propria that are probably fibroblasts. 12 In this cell type Salmonella actively restrain their proliferation.…”
mentioning
confidence: 99%